APPLICATION OF NOVEL GEOSTATISTICS METHODS ON SOUTH TORTKUDUK URANIUM ROLL-FRONT DEPOSIT, CHU-SARYSU, KAZAKHSTAN - Abeuov, Alibek (Nazarbayev University School of Mining and Geosciences, 2024)
Research thesis titled "Application of Novel Geostatistics Methods on South Tortkuduk Uranium Roll-Front Deposit, Chu-Sarysu, Kazakhstan" provides a comprehensive integration of the geological and geostatistical tools and principles related to uranium roll-front deposits. The thesis is a case study of an about 15m thick reservoir unit of the Uyuk Formation (Lower Eocene) in the South Tortkuduk uranium field located in southern Kazakhstan. The study area covers 45 hectares suitable for placing 98 development production cells. The thesis is organized into several sections, delving into the importance of uranium, the geological context of roll-fronts, and the application of advanced geostatistical methods. Methodologically, advanced mapping techniques, including parallel cross-sections coupled with conceptual mapping of three-dimensional geobodies, are employed to delineate reservoir and non-reservoir facies associations (architectural elements), shedding light on the role of sedimentary structures in controlling uranium mineralization. Furthermore, sophisticated 3D modeling in Isatis.neo and Petrel software enables the probabilistic geological simulation (PGS), augmented by the integration of vertical proportion curves (VPC) and horizontal distribution estimation. The culmination of these methodological endeavors reveals novel insights into uranium mineralization dynamics, challenging conventional models by suggesting that sedimentary structures like mud-plug deposits may act as lateral barriers during uranium migration, influencing mineralization distribution within the deposit as seen from both mineralization and facies modeling. This research represents a significant contribution to the field, pushing the boundaries of knowledge in uranium geology and geostatistics. By bridging a comprehensive literature review with advanced modeling techniques, it offers a holistic understanding of roll-front deposits' complexities. The findings not only have implications for predictive models and exploration strategies but also contribute to advancing sustainable energy solutions on a global scale.
Keywords: Type of access: Restricted; Uranium; Roll-front; Geo-modelling; Vertical Proportion Curves; Pluri-Gaussian Simulations